2020 IEEE Second International Conference on Cognitive Machine Intelligence (CogMI) 2020
DOI: 10.1109/cogmi50398.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Ubiquitous Technologies for Remote Worker Wellbeing and Productivity in a Post-Pandemic World

Abstract: In light of the ongoing COVID-19 pandemic, remote work styles have become the norm. However, these work settings introduce new intricacies in worker behaviors. The overlap between work and home can disrupt performance. The lack of social interaction can affect motivation. This elicits a need to implement novel methods to evaluate and enhance remote worker functioning. The potential to unobtrusively and automatically assess such workers can be fulfilled by social media and ubiquitous technologies. This paper si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…When the camera is not turned on, teleworkers' effort and progress were invisible to their peers and supervisors. These mixed attitudes support prior work stating that there is only a thin line of difference in perceiving the same technology for surveillance or for assessment (Das Swain et al 2020). How to balance the support and surveillance of teleworkers should be evaluated further.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…When the camera is not turned on, teleworkers' effort and progress were invisible to their peers and supervisors. These mixed attitudes support prior work stating that there is only a thin line of difference in perceiving the same technology for surveillance or for assessment (Das Swain et al 2020). How to balance the support and surveillance of teleworkers should be evaluated further.…”
Section: Discussionsupporting
confidence: 60%
“…Teleworking limits interactions with co-workers, and also makes it difficult to self-evaluate their performance and be aware of other co-workers' expectations during team collaboration (Das Swain et al 2020). Nicholas Bloom (2020) suggests that an effective "performance review system" to evaluate teleworkers' output is essential to make teleworking succeed.…”
Section: Tools To Facilitate Peer Support and Self-evaluation And To Track Work Progress And Performancementioning
confidence: 99%
“…All the more interesting is the research by Neal, Wood, and Quinn, who found that people tend to perform up to 45% of the activities they perform constantly and out of habit during the day, i.e., in the same context. For example, reading a newspaper on the bus on the way to school, or visiting a fast food restaurant [75]. A pandemic represents a significant intervention in this "everyday life", which affects, among other things, the motivation of an individual in performing daily tasks, and an increase in negative emotions, including the perception of (un)wellbeing [76][77][78].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 has brought a dramatic business environment by disrupting the business networks that imply the flow of knowledge and technological capital, which call for quick reform (Aghion et al , 2021). Moreover, the pandemic has disrupted the business environment in multiple ways, including the changes in work settings that encourage firms to change the entrepreneurial culture to adopt social media and ubiquitous technologies (Swain et al , 2020). It appears that many firms experience excellent performance during the pandemic by adopting the information technology that generates various innovative solutions, whilst others suffer from the lockdown economy.…”
Section: Introductionmentioning
confidence: 99%